Reaksi Pasar Atas Pengungkapan Management Discussion and Analysis - Surata, Putu Aldhi; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 28 No 2 (2019)DO - 10.24843/EJA.2019.v28.i02.p08, 2019)
OJK issues POJK No.29 / POJK.04 / 2016 which requires MD & A disclosure in the  annual report. The purpose of this study is to prove empirically that there are (1) market  reactions in annual report disclosures, (2) the effect of MD & A disclosure level on  abnormal returns. The study population used the KOMPAS100 index of 100 issuers with a  total sample of 63 samples. The Wilcoxon statistical test results state that there are  differences before and after the disclosure of the annual report. Furthermore, a simple  linear regression test was conducted which gave the results that the MD & A disclosure  had a positive effect on the market reaction that was proxied using abnormal return. The  test results produce MD & A disclosures that have a positive effect on market reactions  through abnormal returns so that the market is known to use the information contained in  MD & A. Keywords :  Management discussion and analysis, abnormal return, annual report.